1998
DOI: 10.1177/001872679805100701
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Style and the Theory and Practice of Individual and Collective Learning in Organizations

Abstract: This paper reviews aspects of two largely disparate literatures from the adjacent fields of individual and organizational learning and identifies some implications for theory and practice. The focus of attention is the extent to which the individual level construct cognitive style can be meaningfully applied to aid the understanding of learning at the level of the organization as well as at the level of the individual. Attention is given to the ways in which consideration of cognitive style can improve the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
174
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(194 citation statements)
references
References 33 publications
2
174
0
6
Order By: Relevance
“…Various alternative learning strategies can be discussed and new learning strategies, in addition to their current personal preferences, can be tried out and developed in everyday work and learning processes, leading to a possible improvement in employees' on-the-job learning (Berings et al, 2005). Such instruments can be used to improve the individual job fit, that is, a good fit between learning style and the learning demands of a job, or to manage the composition of a team in order to promote effective learning (Hayes & Allinson, 1998). In this study we have tried to identify those dimensions of on-the-job learning styles that can create an awareness among employees and offer them opportunities to improve their on-the-job learning.…”
Section: Discussionmentioning
confidence: 99%
“…Various alternative learning strategies can be discussed and new learning strategies, in addition to their current personal preferences, can be tried out and developed in everyday work and learning processes, leading to a possible improvement in employees' on-the-job learning (Berings et al, 2005). Such instruments can be used to improve the individual job fit, that is, a good fit between learning style and the learning demands of a job, or to manage the composition of a team in order to promote effective learning (Hayes & Allinson, 1998). In this study we have tried to identify those dimensions of on-the-job learning styles that can create an awareness among employees and offer them opportunities to improve their on-the-job learning.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Nissera UK workforce responded to continuous improvement practices with an orientation to revising production systems that was directed at the future needs of the organization. The role of actors in shaping acquired knowledge was evident in the meanings that were attached to new practices (Hayes and Allinson, 1998). Alternative methods could not be habitualized in instances where the original meaning of Japanese practices, which are embedded in a highlycoordinated national business system, could not be shared by the UK adopters operating in a compartmentalized business system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the environment shapes the use of cognitive styles (Simon 1987) and different situations and our experiences can influence that use (Hayes and Allinson 1998).…”
Section: The Nature and Structure Of Cognitive Stylesmentioning
confidence: 99%
“…The influence of cognitive styles has become evident not only in relation to political judgment, as investigations have shown that the ways in which we perceive information and derive meaning from it are also relevant for decision-making, problem-solving, learning, creativity, and the support of different values (Hayes and Allinson 1998;Kirton 1976;Spicer and Sadler-Smith 2005;Puccio et al 1995;Tetlock 2000;Van Den Broeck et al 2003). …”
Section: Introductionmentioning
confidence: 99%